Toward a revision of the bamboo corals: Part 3, deconstructing the Family Isididae - Saucier, Esprit Heestand; France, Scott C.; Watling, Les (Zootaxa, 2021)
Bamboo corals are distinguished from most other octocorals by an articulated skeleton. The nodes are proteinaceous and sclerite-free while the internodes are composed of non-scleritic calcium carbonate. This articulation of the skeleton was thought to be unique and a strong synapomorphy for the family Isididae. Our phylogeny, based on the amplification of mtMutS and 18S, shows an articulating skeleton with sclerite-free nodes has arisen independently at least five times during the evolutionary history of Octocorallia rather than being a synapomorphy characteristic of a monophyletic bamboo coral clade. The family Isididae is currently composed of four subfamilies (Circinisidinae, Isidinae, Keratoisidinae, and Mopseinae). Not only is the family polyphyletic, but our genetic analyses suggest also the subfamily Isidinae is polyphyletic based on current taxonomic classifications, and Mopseinae is not monophyletic. The type, Isis, is found outside of the well-supported Calcaxonia – Pennatulacea clade where the other members of Isididae cluster. The current classification of the family Isididae does not reflect the evolutionary history of an articulated skeleton. To better reflect the evolutionary history of these taxa we propose that three of the four the subfamilies, the genus Isidoides, and genera within the subfamily Isidinae, be elevated to family level to produce a classification with five families with a bamboo-like skeleton: Chelidonisididae, Isididae, Isidoidae, Keratoisididae, and Mopseidae.